2020
DOI: 10.1021/acs.jpclett.9b03487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chiral Molecules on the Electron’s Spin Wavefunction at Interfaces

Abstract: Kelvin-probe measurements on ferromagnetic thin film electrodes coated with self-assembled monolayers of chiral molecules reveal that the electron penetration from the metal electrode into the chiral molecules depends on the ferromagnet’s magnetization direction and the molecules’ chirality. Electrostatic potential differences as large as 100 mV are observed. These changes arise from the applied oscillating electric field, which drives spin-dependent charge penetration from the ferromagnetic substrate to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 80 publications
(116 citation statements)
references
References 44 publications
(61 reference statements)
8
106
0
Order By: Relevance
“…Put more simply, for one spin orientation the connection of the antibody to the charge reservoir in the substrate is better than that for the other spin orientation, allowing for more facile charge flow. 14 When more electrons flow into or away from the antibody, its internal charge distribution is dynamically modulated in a way that enhances its interaction with the antigen, thereby increasing the rate of binding between the two. This experiment therefore establishes modulation of charge distribution as a means to allosterically affect PPA kinetics, an effect we term charge-reorganization allostery.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Put more simply, for one spin orientation the connection of the antibody to the charge reservoir in the substrate is better than that for the other spin orientation, allowing for more facile charge flow. 14 When more electrons flow into or away from the antibody, its internal charge distribution is dynamically modulated in a way that enhances its interaction with the antigen, thereby increasing the rate of binding between the two. This experiment therefore establishes modulation of charge distribution as a means to allosterically affect PPA kinetics, an effect we term charge-reorganization allostery.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Humans and constituent chiral biomolecules are forms of condensed matter ( van der Gucht, 2018 ; Marx, 2020a ); however current theories and frameworks in the biological sciences are predominately governed by classical electrostatics (the electron's charge is the sole determinant of biochemical reactions) ( Honig and Nicholls, 1995 ); therefore, perturbations in the spin state of electrons in chiral biomolecules are assumed to be unimportant, and relevant concepts in condensed matter physics are ignored. The discovery of the chiral-induced spin selectivity effect in chiral biomolecules suggests that an external magnetic field could alter the spin state of electrons in chiral biomolecules and result in the magnetic catalysis of aberrant molecules and pathology in humans and other animals; however, the role of magnetic catalysis in a pandemic has not been explored ( Ghosh et al, 2020 ; Naaman et al, 2019a ; Naaman, 2019 ). Indeed, Naaman et al recently demonstrated that chiral biomolecules-ferromagnetic interfaces mediate spin polarization-induced enantioselective crystallization of biomolecules ( Naaman, 2019 ; Naaman et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…This effect is referred to as the chiral induced spin selectivity (CISS) and serves as an effective valve for the flow of electrons from the surface into the adsorbed protein molecules. 11 It can therefore lead to either acceleration or retardation of antibody–antigen association kinetics, depending on the orientation of the substrate’s magnetization.…”
mentioning
confidence: 99%